Coastal tourism, sustainability, and climate change in the Caribbean beaches and hotels - Honey, Martha; Hogenson, Samantha; Stringnam, Betsy Bender (Tourism and hospitality management collection)
"The Caribbean is the most tourism-dependent region in the world, and its tourism attractions and infrastructure and three-quarters of its people are concentrated along its coastlines. While the Caribbean contributes to less than 1 percent of global carbon emissions, its beaches and hotels are among the most vulnerable to climate impacts, including increasingly fierce and frequent hurricanes, sea-level rise, and loss of coral and mangroves. This book details many techniques for mitigating and adapting to climate impacts and demonstrates how socially and environmentally responsible companies are proving resilient in coping with climate change." --